The priming of stimulus-elicited involuntary mental imagery - Christina Y. Wong; Alejandro Heredia Cedillo; Ezequiel Morsella (Acta Psychologica, 2024)
Percepts, urges, and even high-level cognitions often enter the conscious field involuntarily. The Reflexive Imagery Task (RIT) was designed to investigate experimentally the nature of such entry into consciousness. In the most basic version of the task, participants are instructed not to subvocalize the names of visual objects. Involuntary subvocalizations arise on the majority of the trials. Can these effects be influenced by priming? In our experiment, participants were exposed to an auditory prime 300 ms before being presented with the RIT stimuli. For example, participants heard the word “FOOD” before seeing two RIT stimuli (e.g., line drawings of BANANA and CAT, with the former being the target of the prime). The short span between prime and target allowed us to assess whether the RIT effect is strategic or automatic. Before each trial, participants were instructed to disregard what they hear, and not to think of the name of any of the objects. On an average of 83% of the trials, the participants thought (involuntarily) of the name of the object associated with the prime. This is the first study to use a priming technique within the context of the RIT. The theoretical implications of these involuntary effects are discussed.